PELAYANAN PUBLIK DI KECAMATAN BANGKO PUSAKO KABUPATEN ROKAN HILIR TAHUN 2011-2013(STUDI PENCATATAN SIPIL DAN KEPENDUDUKAN) - Saragih, Rio Pinda; Suryadi, Heri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The purpouse of this study to determine How Public Servise the Kecamatan Bangko Pusako Kabupaten Rokan Hilir 2011-2013 years.The method used is qualitative method of data descriptive assessment. Object of this study is the Kecamatan Bangko Pusako Kabupaten Rokan Hilir. The technique of collecting data using interviews, observation, and documentation.By using key informants as a source of information which amounts to 38 people.Based on the research that has been to know how public servise the Kecamatan Bangko Pusako 2011-2013 years. Where us public servise the Kecamatan Bangko Pusako is not optimal. The public servise in Kecamatan Bangko Pusako is not optimal, many problem in public servise as procedure, on time the public servise, cost expens, produc, tools, and official competention the Kecamatan Bangko Pusako Kabupaten Rokan Hilir.Keywords : Servise, Public Servise, the Kecamatan